EPID-18. NATIONAL TRENDS IN THE USE OF TARGETED AND IMMUNOTHERAPY IN THE UP FRONT MANAGEMENT OF GLIOBLASTOMA - Wegner, Rodney (Neuro Oncol, 2019)
BACKGROUND: Current standard of care for GBM involves an aggressive multimodality approach including surgical resection followed by adjuvant chemoradiation. Despite this approach, overall survival remains poor and treatment approaches continue to evolve. Given the successes of immunotherapy in other disease sites, implementation in GBM management may improve outcomes. METHODS: We conducted this retrospective NCDB study to analyze treatment trends and outcomes from 2004–2015 regarding immunotherapy for GBM. We excluded patients treated without surgery, extracranial radiation, or chemotherapy as well as those lost to follow up. RESULTS: Of the 39,317 eligible patients in this study, 511 were treated with immunotherapy and 38,806 lack thereof. Median overall survival for all patients was 15 months with a 2 and 5 year survival rate of 29% and 8%, respectively. Factors influencing delivery of immunotherapy included younger age, higher income, facility location in a metropolitan location, greater distance to the treatment facility, treatment at an academic facility, treatment outside of the years 2007 to 2009, and Caucasian race. On propensity matched analysis, survival was 18 months and 17 months with and without immunotherapy, respectively (p=0.15). Higher comorbidity, lower income, and male gender predicted for worse survival. CONCLUSIONS: The results of this analysis show an initial decrease and then increase in the use of immunotherapy in the management of GBM. Propensity-matched analyses did not show an overall survival benefit.